2020
DOI: 10.1186/s12302-020-00314-9
|View full text |Cite
|
Sign up to set email alerts
|

A European proposal for quality control and quality assurance of tandem mass spectral libraries

Abstract: Background: High resolution mass spectrometry (HRMS) is being used increasingly in the context of suspect and non-targeted screening for the identification of bioorganic molecules. There is correspondingly increasing awareness that higher confidence identification will require a systematic, group effort to increase the fraction of compounds with tandem mass spectra available in central, publicly available resources. While typical suspect screening efforts will only result in tentative annotations with a modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 53 publications
(102 reference statements)
0
59
0
Order By: Relevance
“…As the number of online compound databases have increased the last years, the performance of HR-MS instrumentation and proposals for quality control of the databases have likewise come into focus. The improvement of instrument performance and better database standardisation have facilitated the transferability of detected diagnostic fragment ions among databases, thereby promoting overall the usability and robustness of databases [ 12 , 13 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the number of online compound databases have increased the last years, the performance of HR-MS instrumentation and proposals for quality control of the databases have likewise come into focus. The improvement of instrument performance and better database standardisation have facilitated the transferability of detected diagnostic fragment ions among databases, thereby promoting overall the usability and robustness of databases [ 12 , 13 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since spider venoms were only available in limited amounts, the focus of the MS/MS acquisition method has been placed on a high duty cycle and an optimal collision energy for polyamine derivatives instead of data collected at different collision energies as recently recommended by the metabolomics community [36]. This results in a highest sensitivity and a better distribution of fragment ions over the entire mass range and simplifies the visual comparison between measured spectra and those obtained from the FRIOC fragmentation tool (see above).…”
Section: Standardized Analytical Methods (Sam2020)mentioning
confidence: 99%
“…Interestingly, they also revealed that under certain collision energies time of flights ((TOF)s) and Orbitrap fragmentation spectra are comparable. 104 …”
Section: Harmonization and Reference Materialsmentioning
confidence: 99%